Role of railways in empowering travelers: A case study from the Czech Republic. Issue 2 (August 2015) - Jade, Radhika; Molková, Tatiana; Kvizda, Martin
Highlights The study presents traveler empowerment as an enduring marketing strategy for passenger railway operators in the Czech Republic. To identify major 'railway constructs' that result in the subjective experience of empowerment among the travelers. To test the 'traveler empowerment model' quantitatively. To provide unique and enduring marketing strategies to Czech railway operators based on their unique selling propositions (USPs).